Attitude and perception of medical interns towards abortion in a teaching hospital in central Nepal - Pradhan, Manohar; Subedi, Nuwadatta (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: The objectives the study was to explore the, attitude and perception of medical interns, who are in the verge of being registered medical practitioners about abortion care services in Nepal. Materials & Methods: This is a questionnaire based descriptive-cross-sectional study conducted among the 96 interns of the College of Medical Sciences. The questionnaire was semi structured consisting of questions on self-assessed educational program characteristics, attitudes and perceptions regarding abortions in the context of Nepal. Results: The response rate of the participants was 88.07%. The mean age of the respondents was 24.43±1.449 years. A total of 65 (67.7%) responded that the topic of reproductive health was adequately covered in their course of study and 31 (32.3%) opined that the topic was somewhat covered. Only two of the respondents self-assessed that their theoretical knowledge of sexual and reproductive health was very good while 68 (70.8%) told that it was good and 26 (27.1%) graded themselves as having just fair knowledge in the field. Twenty four (25.0%) responded that they had clinical practice in abortion care services during their course of study. Conclusion: The medical interns had been adequately exposed to the reproductive health though they had less clinical practice on abortion care services. The attitude and perceptions of the future health care providers should be understood to properly orient them to the clinical practice.